Screening of cowpeas for resistance to Clavigralla tomentosicollis Stal (Hemiptera: Coreidae) - Jackai, L.E.N. (Oxford University Press, 1990)
A laboratory screening method was developed for evaluating resistance of cowpea, Vigna unguiculata (L.) Walp, to Clavigralla tomentosicollis Stål. The technique uses dry cowpea seeds, which were judged better than fresh seeds or fresh pods, to identify protracted nymphal development and high cohort mortality. Two wild cowpea relatives, TVNu 72 and TVNu 73, were highly resistant to C. tomentosicollis. Insect mortalities were >85% on the resistant lines as compared to <25% on the susceptible lines. Survivors on the resistant lines had extended developmental times. The resistant lines are highly pubescent but pubescence may not be the major factor responsible for this resistance. Laboratory results compared well with those obtained from greenhouse findings and field tests, giving correlation coefficients (r) of 0.96 and 0.85, respectively. The laboratory screen is accurate, fast, and inexpensive.